A haem-peroxidase from the seeds of Araujia sericifera: Characterization and use as bio-tool to remove phenol from aqueous solutions. (July 2019) - Landi, Nicola; Ragucci, Sara; Letizia, Francesco; Fuggi, Amodio; Russo, Rosita; Pedone, Paolo V.; Di Maro, Antimo
Abstract: Plants seeds are an important source of enzymes with biotechnological interest. In particular, plant peroxidases, because of their enzymatic activity and stability, are used for the synthesis of phenolic resins, in the treatment of waste waters, or as labelling enzymes and in food industry. Thus, these enzymes can give a potential substitute of other polluting industrial catalysts to the conservation of the environment. In the present work, a novel plant peroxidase (named As-sP) was purified and characterised from seeds of Araujia sericifera . This enzyme (∼40 kDa) exhibits a maximum activity at pH 5.0 and is a haem-peroxidase, basing on both the spectroscopic properties and amino acid composition. As-sP activity increased by Ca 2+, Cu 2+, Mg 2+ ; while in presence of EDTA, it is lost. On the other hand, As-sP activity is stable in a range of 40–60 °C, while decreased at higher temperature (70–80 °C). Furthermore, the activity has been tested in presence of natural (chlorogenic acid, pyrogallol and guaiacol) or synthetic (ABTS) substrates, finding that chlorogenic acid (Km 38.6 ± 2.4 μM and Vmax 92.6 ± 3.9 μM min −1 ) was the most suitable. Finally, this enzyme was able to remove phenol from water solutions, and this capacity increases in presence of Ca 2+ and polyethylene glycol. This novel peroxidase, due to its enzymatic properties and heat stability, is a novel tool for bioremediation and can be used as a beneficial candidate for industrial applications, such as in decontamination of phenol-polluted waters. Graphical abstract: Image 1 Highlights: Peroxidase, named As-sP, from cruel vine has been characterized. Spectroscopic properties/amino acid composition show that As-sP is a haem-protein. As cofactors, Ca 2+, Cu 2+ and Mg 2+ enhanced As-sP activity. As-sP promotes phenol precipitation in water. As-sP as raw soluble proteins from cruel vine seeds are a bio-tool for bioremediation.